Adipogenesis is Under Surveillance of Hsp90 and the High Molecular Weight Immunophilin FKBP51 - Toneatto, Judith (2015)
Adipose tissue plays a central role in the control of energy balance as well as in the maintenance of metabolic homeostasis. It was not until recently that the first evidences of the role of heat shock protein (Hsp) 90 and high molecular weight immunophilin FKBP51 have been described in the process of adipocyte differentiation. Recent reports describe their role in the regulation of PPARγ, a key transcription factor in the control of adipogenesis and the maintenance of the adipocyte phenotype. In addition, novel roles have been uncovered for FKBP51 in the organization of the architecture of the nucleus through its participation in the reorganization of the nuclear lamina. Therefore, the aim of this review is to integrate and discuss the recent advances in the field, with special emphasis on the roles of Hsp90 and FKBP51 in the process of adipocyte differentiation.